2010
DOI: 10.1177/0142723709359241
|View full text |Cite
|
Sign up to set email alerts
|

Gender and patterns of language development in mother-toddler and father-toddler dyads

Abstract: The study examined parent, child, and dyadic gender effects in parent reports of words and MLUs. Mothers and fathers from 113 families completed the MacArthur Communicative Development Inventory: Toddlers when the toddlers were 1;7; half completed a follow-up at 2;0. Child gender differences in words and MLUs increased over time and parent gender differences decreased. Dyadic analyses revealed bidirectional influences. At 1;7, dyadic scores for words and MLUs displayed a descending pattern from mother—daughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 75 publications
2
42
1
5
Order By: Relevance
“…Although such an advantage has been reported for other languages, it seems to be modulated by the type of language skills mastered and the age range, with receptive vocabulary and different ages not showing gender effects or only displaying weak effects (Bornstein et al, 2004;Eriksson et al, 2012;Jackson-Maldonado et al, 2013;Lovas, 2011). In our findings, girls clearly outperformed boys, already at the infant stage and increasing with age.…”
Section: Discussioncontrasting
confidence: 66%
“…Although such an advantage has been reported for other languages, it seems to be modulated by the type of language skills mastered and the age range, with receptive vocabulary and different ages not showing gender effects or only displaying weak effects (Bornstein et al, 2004;Eriksson et al, 2012;Jackson-Maldonado et al, 2013;Lovas, 2011). In our findings, girls clearly outperformed boys, already at the infant stage and increasing with age.…”
Section: Discussioncontrasting
confidence: 66%
“…This may reflect a difference in emotional expressiveness with infant boys having an immature nervous system and greater irritability and need for soothing compared with girls. 12,35 The prelinguistic vocalizations analyzed in this study, however, may be different from the extensively studied meaningful speech that develops beyond the first year of life.…”
Section: Figurementioning
confidence: 86%
“…Girls have been shown to have earlier brain maturation, eye contact, and joint attention, which may in turn influence greater maternal responsiveness. 12,25,26 A significant gap in language input from fathers may have long-term implications. Recent studies have shown that fathers' language input and vocabulary spoken to infants and young children may also be a predictor of child language outcomes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Early vocabulary is thus relevant when assessing developmental trajectories and risks (Henrichs et al, 2011 ; Lee, 2011 ; Ullrich & von Suchodoletz, 2011). Frequently discussed environmental characteristics influencing early vocabulary include type and quality of care (e.g., Ebert et al., 2013 ; Rodriguez & Tamis-LeMonda, 2011), interaction patterns of caregivers that might differ according to the child’s gender (Johnson, Caskey, Rand, Tucker, & Vohr, 2014 ; Lovas, 2011 ; Sung, Fausto-Sterling, Garcia Coll, & Seifer, 2013), and the mono- or multilingual composition of the language input children receive (e.g., Byers-Heinlein, 2013 ; Quiroz, Snow, & Zhao, 2010). In this study, we assessed the predictive value of gender, type and duration of early care, and monolingual versus bilingual family environment for the size and composition of 2-year-olds’ expressive German vocabulary.…”
Section: Introductionmentioning
confidence: 99%